Avaliação genotóxica e histológica em peixes (hyphessobrycon heterorhabdus) do igarapé Cararazinho expostos ao chorume da lixeira pública de Santarém – PA - PEREIRA, Heveline Campos (Universidade Federal do Oeste do Pará, 2021)
The enormous garbage production is one of the major environmental issues in the present. The inappropriate discard and management of garbage give serious risks to the human and ecosystem health. The leachate, liquid produced by garbage decomposition, may contains harmful molecules that damage the genetic material, such as heavy metals and aromatic polycyclic hydrocarbon (APH). The present study goals to evaluate the genotoxic and histopathological effects of the leachate from Santarém Landfill Dump in fishes - Hyphessobrycon heterorhabdus. Micronucleus, erythrocyte nuclear abnormalities techniques and comet assay were conducted for the genotoxicity evaluation, while tissue injuries were assessed with gills and liver histological preparations. The fishes were exposed to leachate (10, 5 and 2%), to natural stream Cararazinho’s water and to 20ppm benzene. The genotoxicity biomarkers do not evidenced significant variation between exposed and control group (stream natural water). Gills and liver showed diverse types of tissue lesions. Therefore, under the light of these results we conclude that Cararazinho’s stream water, because receives leachate from the Santarém Landfill Dump, plays to the occurrence of genotoxic and tissue damages in fishes H. heterorhabdus.